Performance Analysis of Multilayered Multipriority Asymmetric-Sized Delta Networks - Vasiliadis, D. C.; Rizos, G. E.; Vassilakis, C. (Journal of Computer Networks and Communications, 2011)
The performance of multilayered asymmetric-sized finite-buffered delta networks supporting multiclass routing traffic is presented and analyzed in the uniform traffic conditions under various loads using simulations. The rationale behind introducing asymmetric-sized buffered systems is to have a better exploitation of available buffer spaces, while the implementation of multilayered architecture is applied in order to further improve the overall performance of network. The findings of this performance evaluation can be used by network designers for drawing optimal configurations while setting up the network, so as to best meet the performance and cost requirements under the anticipated traffic load and quality of service specifications.